CONSIDERATIONS ON REAL TIME DATA WAREHOUSING (RTDW) - Marius Bogdan DINU (Fiabilitate şi Durabilitate)
The RTDW concept originated in the early 2000s. By that time, computing power had increased to a level that was allowing extraction of data collections for reporting purposes. Such collections were used almost in real time and at speeds nearly comparable to what an operation system was capable to deliver. The main idea will be to eliminate some of the components of the classic extraction process which is basically the most costly factor less time - consuming. We anticipate that the following factors will be decisive: elimination of batch-type processes [1], data compression techniques, data capture techniques, ability to keep in cache a large volume of data, parallel processing, and data mining algorithms that can adapt to such applications.